Taking introductory physics in studio, lecture, or online format: What difference does it make in subsequent courses, and for whom? - Gerd Kortemeyer; Christine Kortemeyer; Wolfgang Bauer (Physical Review Physics Education Research, 2023)
At large institutions of higher education, students frequently have a choice whether to attend the introductory physics sequence asynchronously online, on-site in a traditional lecture setting, or in a reformed studio setting. In this study, we investigate how these different settings are correlated with measures of self-efficacy, interest in physics, and success in subsequent physics and engineering courses, which have the introductory physics sequence as prerequisites. As previous research indicates, some of these measures may depend on gender. We found that the course setting had no significant correlation with the grade in subsequent courses, but that studio settings gave students the feeling of being better prepared, particularly for subsequent courses that included laboratory or recitation components. We also found that gender was correlated with measures of interest in physics, where female students expressed significantly less interest in the subject, regardless of course setting.